Brief interactive lifestyle preventive medicine video education in the primary care clinic: Protocol for a randomized clinical trial - Dylan Luke Arroyo; Daniel Keyes; Ghadah W. Abdulshafi; Ali Jafri; Hemica Hasan; David Steinberger; Batoul Dabajeh; Alice Nassar; Anukul Karn; Rachel Nkrumah; Preanka Dhanoa; Kerby Shedden (PLoS ONE, 2026)
Introduction Preventive counseling improves long-term health, but primary care clinicians face time constraints limiting patient education. In a prior emergency department pilot study, a brief passive video trended towards increased patients’ willingness to change health behaviors. The current trial, conducted at the primary care clinic, evaluates the feasibility and impact of a short, interactive prevention video delivered during a primary care office visit. Methods and analysis We will conduct a prospective, randomized, non-blinded clinical trial among adult patients presenting to a primary care clinic. Immediately after their appointment, participants will be randomized to receive either the interactive prevention video or usual care. The video maintains engagement through simple in-video questions and adapts content based on patient responses (e.g., skipping smoking cessation for non-smokers). After the encounter, all participants will complete surveys assessing readiness and confidence to initiate lifestyle change including a transtheoretical “readiness ruler.” Survey items will be drawn from validated instruments, including the Gillespie & Lenz Readiness and Confidence to Participate in Lifestyle Activities Surveys, the Pittsburgh Sleep Quality Index (PSQI), and select questions from the U.S. Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) Survey. Patients will be asked for medical record access and permission for follow-up contact. Outcomes The primary outcome is index-visit Lifestyle Readiness and Confidence to Change scores. Secondary outcomes include satisfaction with the clinic visit, intention to change specific lifestyle behaviors, and healthcare use outside the clinic at 30 days and 6 months, as assessed via record review. A 3–12-month follow-up survey will assess self-reported lifestyle changes and new diagnoses. Statistical plan and sample size Analyses will follow intention-to-treat. Ordinal logistic regression will compare primary outcomes between arms, adjusting for Charlson Comorbidity Index, age, sex, gender, and prespecified predictors. Logistic regression will evaluate binary follow-up outcomes. Complete-case analyses will be used, and differential attrition will be reported. We plan to enroll approximately 350 patients. Trial registration ClinicalTrials.gov NCT06730737.